The Sunna and its Status in Islamic Law
IX, 256 p.
Keywords: This volume provides an overview of the nature and scope of the concept of Sunna both in pre-modern and modern Islamic discussions. The main focus is on shedding more light on the context in which the term Sunna in the major works of Islamic law and legal theory across all of the major madhahib was employed during the first six centuries Hijri.